Analisis Penerapan Audit Internal Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) pada Perusahaan X Hulu Migas - Dwi Hidayatullah, Muhammad; Novrikasari, Novrikasari; Windusari, Yuanita; Alam Fajar, Nur (Jurnal Ilmiah Administrasi Publik, 2024)
This study investigates the execution of internal audits for the Occupational Safety and Health Management System (SMK3) in upstream oil and gas businesses. Literature studies are employed to elucidate the application of SMK3 in companies, particularly in the upstream oil and gas sector. The findings of this study demonstrate that the application of the Occupational Safety and Health Management System (SMK3) in upstream oil and gas companies can be effectively executed by adhering to the Plan-Do-Check-Action (PDCA) principles. The objective is to ensure that the implementation of SMK3 progresses as planned, is executed in accordance with the plan, includes adequate control and supervision, and incorporates measures to enhance K3 performance. In addition, internal audits are necessary to assess and analyze K3 policies and enhance organizational processes, with the ultimate goal of attaining zero accidents. The implementation of Oil and Gas SMK3 necessitates the active involvement of all employees within an organization or enterprise.